Chronic Cadmium Intoxication and Renal Injury Among Workers of a Small-scale Silver Soldering Company - Choi, Won-Jun; Kang, Seong-Kyu; Ham, Seunghon; Chung, Wookyung; Kim, Ae Jin; Kang, Myunghee (Safety and health at work, 2020)
Cadmium exposure may induce chronic intoxication with renal damage. Silver soldering may be a source of cadmium exposure. We analyzed working environment measurement data and periodic health screening data from a small-scale silver soldering company with ten workers. Concentrations of cadmium in air from working environment measurement data were obtained. Concentrations of blood and urinary cadmium, urine protein, and urine β2-microglobulin (β2M) were obtained. The generalized linear model was used to identify the association between blood and urine cadmium and urine β2M concentrations. Clinical features of chronic cadmium intoxication focused with toxicological renal effects were described. The mean duration of work was 8.5 years (standard deviation [SD] = 6.9, range = 3–20 years). Cadmium concentrations in air were ranged from 0.006 to 0.015 mg/m3. Blood cadmium concentration was elevated in all ten workers, with a highest level of 34.6 μg/L (mean = 21.288 μg/L, SD = 11.304, range = 9.641–34.630 μg/L). Urinary cadmium concentration was elevated in nine workers, with a highest level of 62.9 μg/g Cr (mean = 22.151 μg/g creatinine, SD = 19.889, range = 3.228–62.971 μg/g creatinine). Urine β2M concentration was elevated in three workers. Urinary cadmium concentration was positively associated with urine protein concentration (beta coefficient = 10.27, 95% confidence interval = [4.36, 16.18]). Other clinical parameters were compatible with renal tubular damage. Cadmium intoxication may occur at quite low air concentrations. Exposure limit may be needed to be lowered.